Procurement with Costly Bidding, Optimal Shortlisting, and Rebates - Cuihong Fan; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We consider the procurement of a complex, indivisible good when bid preparation is costly, assuming a population of heterogeneous contractors. Shortlisting is introduced to implement the optimal number of bidders, and we explore whether the procurer should reimburse the nonrecoverable cost of preparing a bid in whole or in part. We find that a reimbursement policy is profitable for the procurer only if performance and bidding costs are negatively correlated. Moreover, negative rebates (entry fees) always dominate positive rebates.
urn:nbn:de:bvb:19-epub-13385-7
Keywords: D44; D45; 330; Procurement; Auctions; Entry